TECHNOLOGICAL SUPPORT FOR PROTON THERAPY - Elmurotova Dilnoza Baxtiyorovna; Fayziyeva Nodira Alisherovna (Web of Journals Publishing, 2025)
The paper reviews the main parts of proton therapy: cyclotron, beam transport system, and irradiation unit with a radiation head. Several advantages of proton therapy, which is an alternative to surgical procedures.
Keywords: Proton therapy, cyclotron, head, dose, cancer, tumor, chordoma, transportation, collimator, clinic, surgery.